Las técnicas grafo plásticas y su incidencia en la iniciación de la lectura y escritura de los niños y niñas del primer año de educación básica de la escuela Miguel Fiofrío nº1 de la ciudad de Loja período 2013 - Pucha Torres, Liliana del Cisne (2014)
This present study is limited in the analysis of "GRAPH VISUAL TECHNIQUES AND ITS IMPACT ON THE INITIATION OF READING AND WRITING CHILDREN FIRST YEAR BASIC EDUCATION SCHOOL MIGUEL RIOFRIO No 1. Loja CITY YEAR 2013 "is a theoretical-practical. General Aims To determine whether visual graph techniques affect the initiation of reading and writing children's first year of basic education. Took place with the participation of 27 people, of whom 24 were children and three teachers at the school. To perform this research work was used the following methods: scientific, analytic-synthetic, inductive, deductive and statistical; applied instruments such as psychology survey the teachers and intellectual maturity test for the prognosis of motor learning to read and writing. After analyzing the information obtained from teachers and children came to the conclusion: That by graph techniques developed plastic children fine motor that will help them start writing and reading. It is recommended to continue to use plastic graph technique, using materials such as paper, needles, clay, rubber others. To develop fine psychomotor.